Characterization of the Transcriptome of the Xerophyte Ammopiptanthus mongolicus Leaves under Drought Stress by 454 Pyrosequencing. - Tao Pang; Lili Guo; Donghwan Shim; Nathaniel Cannon; Sha Tang; Jinhuan Chen; Xinli Xia; Weilun Yin; John E Carlson (PLoS ONE)
Background Ammopiptanthus mongolicus (Maxim. Ex Kom.) Cheng f., an endangered ancient legume species, endemic to the Gobi desert in north-western China. As the only evergreen broadleaf shrub in this area, A. mongolicus plays an important role in the region's ecological-environmental stability. Despite the strong potential of A. mongolicus in providing new insights on drought tolerance, sequence information on the species in public databases remains scarce. To both learn about the role of gene expression in drought stress tolerance in A. mongolicus and to expand genomic resources for the species, transcriptome sequencing of stress-treated A. mongolicus plants was performed. Results Using 454 pyrosequencing technology, 8,480 and 7,474 contigs were generated after de novo assembly of RNA sequences from leaves of untreated and drought-treated plants, respectively. After clustering using TGICL and CAP3 programs, a combined assembly of all reads produced a total of 11,357 putative unique transcripts (PUTs). Functional annotation and classification of the transcripts were conducted by aligning the 11,357 PUTs against the public protein databases and nucleotide database (Nt). Between control and drought-treated plants, 1,620 differentially expressed genes (DEGs) were identified, of which 1,106 were up-regulated and 514 were down-regulated. The differential expression of twenty candidate genes in metabolic pathways and transcription factors families related to stress-response were confirmed by quantitative real-time PCR. Representatives of several large gene families, such as WRKY and P5CS, were identified and verified in A. mongolicus for the first time. Conclusions The additional transcriptome resources, gene expression profiles, functional annotations, and candidate genes provide a more comprehensive understanding of the stress response pathways in xeric-adapted plant species such as A. mongolicus.